Salmonella Typhi Porins OmpC and OmpF Are Potent Adjuvants for T-Dependent and T-Independent Antigens - Pérez-Toledo, Marisol; Valero-Pacheco, Nuriban; Pastelin-Palacios, Rodolfo; Gil-Cruz, Cristina; Perez-Shibayama, Christian; Moreno-Eutimio, Mario A.; Becker, Ingeborg; Pérez-Tapia, Sonia Mayra; Arriaga-Pizano, Lourdes; Cunningham, Adam F.; Isibasi, Armando; Bonifaz, Laura C.; et al. (Frontiers in Immunology, 2017)
Several microbial components, such as bacterial DNA and flagellin, have been used as experimental vaccine adjuvants because of their inherent capacity to efficiently activate innate immune responses. Likewise, our previous work has shown that the major Salmonella Typhi (S. Typhi) outer membrane proteins OmpC and OmpF (porins) are highly immunogenic protective antigens that efficiently stimulate innate and adaptive immune responses in the absence of exogenous adjuvants. Moreover, S. Typhi porins induce the expression of co-stimulatory molecules on antigen-presenting cells through TLR canonical signaling pathways. However, the potential of major S. Typhi porins to be used as vaccine adjuvants remains unknown. Here, we evaluated the adjuvant properties of S. Typhi porins against a range of experimental and clinically relevant antigens. Co-immunization of S. Typhi porins with ovalbumin (OVA), an otherwise poorly immunogenic antigen, enhanced anti-OVA IgG titres, antibody class switching, and affinity maturation. This adjuvant effect was dependent on CD4+ T-cell cooperation and was associated with an increase in IFN-γ, IL-17A, and IL-2 production by OVA-specific CD4+ T cells. Furthermore, co-immunization of S. Typhi porins with an inactivated H1N1 2009 pandemic influenza virus experimental vaccine elicited higher hemagglutinating anti-influenza IgG titres, antibody class switching, and affinity maturation. Unexpectedly, co-administration of S. Typhi porins with purified, unconjugated Vi capsular polysaccharide vaccine (Vi CPS)—a T-independent antigen—induced higher IgG antibody titres and class switching. Together, our results suggest that S. Typhi porins OmpC and OmpF are versatile vaccine adjuvants, which could be used to enhance T-cell immune responses toward a Th1/Th17 profile, while improving antibody responses to otherwise poorly immunogenic T-dependent and T-independent antigens.